Sosialisasi Pemanfaatan Museum Sebagai Sumber Belajar Sejarah Lokal Pada Guru Sejarah Se Kota Pontianak - Haris Firmansyah; Astrini Eka Putri; Ika Rahmatika Chalimi; Hadi Wiyono; Andang Firmansyah (Universitas Mathla'ul Anwar Banten, 2022)
SOCIALIZATION OF THE USE OF MUSEUMS AS A SOURCE OF LOCAL HİSTORY LEARNİNG FOR HİSTORY TEACHERS İN PONTİANAK CİTY. Based on the team's observations that have been stated above, the team feels it is important to carry out socialization activities regarding the use of museums as a source of learning local history to history teachers. So that this museum can be one of the interesting learning experiences in history learning. The expected objectives of this program are as follows: (1) The history of the establishment of the West Kalimantan Museum. (2) Implementation of the use of the West Kalimantan Museum as a source of local history by history teachers throughout the city of Pontianak. And (3) To find out the efforts of the museum and teachers in utilizing the West Kalimantan Museum as a source of learning local history by history teachers throughout the city of Pontianak. The target community involved in the implementation of this activity are all teachers of history subjects in the city of Pontianak. The location for the implementation of the activity is planned in the West Kalimantan Museum Hall in Pontianak City. This activity is carried out through lecture and discussion methods. As a result of this activity, participants consisting of history teachers were able to understand the material regarding the use of museums as a source of learning local history in improving student learning activities in history subjects. The understanding of the participants (teachers) was shown through their enthusiasm in discussing and asking questions about the socialization material.